1999
DOI: 10.1021/jm9902638
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Antitumor Sulfonamides Targeting G1 Phase of the Cell Cycle

Abstract: Described herein is the discovery of a novel series of antitumor sulfonamides targeting G1 phase of the cell cycle. Cell cycle control in G1 phase has attracted considerable attention in recent cancer research, because many of the important proteins involved in G1 progression or G1/S transition have been found to play a crucial role in proliferation, differentiation, transformation, and programmed cell death (apoptosis). We previously reported our first antitumor sulfonamide E7010 as a novel tubulin polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(193 citation statements)
references
References 33 publications
4
188
0
1
Order By: Relevance
“…It must be also mentioned that an antitumor sulfonamide, E7070 (107), recently reported by Owa's group, 105 is in phase II clinical trials in Europe as a novel anticancer agent. 24 As far as we know, this compound has not been assayed as a CA I, by possessing the unsubstituted sulfonamide moiety we predict that it behaves as a strong inhibitor.…”
Section: Antitumor Sulfonamidesmentioning
confidence: 99%
“…It must be also mentioned that an antitumor sulfonamide, E7070 (107), recently reported by Owa's group, 105 is in phase II clinical trials in Europe as a novel anticancer agent. 24 As far as we know, this compound has not been assayed as a CA I, by possessing the unsubstituted sulfonamide moiety we predict that it behaves as a strong inhibitor.…”
Section: Antitumor Sulfonamidesmentioning
confidence: 99%
“…Further synthesis of a large number of sulphonamides revealed that certain N-(7-indolyl)benzenesulphonamides, notably compound E7070, also had antiproliferative properties but that these were not due primarily to antimitotic effects but due to a block in progression through G 1 -phase [103]. Although the main cellular target for compound E7070 has not as yet been identified, it is possible that CDK inhibition may be involved.…”
Section: New Compoundsmentioning
confidence: 99%
“…In our study, they showed activity comparable to that of the standard drug (with IC 50 of 0.012 µM) against the four selected cell lines. Free sulfonamide group was a common Scheme 3 feature in these two compounds; such moiety was reported to play a crucial role in CA inhibition and antitumor activity [7][8][9][10][11][12][13][14][15] . Condensing the sulfonamide moiety with different isocyanates produced the disubstituted sulfonylureido derivatives 9-11 and 22-24 of which compounds 10, 22 and 23 exhibited good antitumor activity against the tested cell lines, but they were less active than the parent sulfonamide derivative; compound 16 displayed moderate antitumor activity against hepatoma cancer cell line and good activity against the other cell lines, compound 17 was active against human beast as well as colon cancer cell lines and moderate activity against human cervix cell line.…”
Section: Pharmacologymentioning
confidence: 99%
“…In that context, several quinazoline derivatives have been shown to exhibit high affinity for receptor tyrosine kinases, as well as other oncogenic targets 5,6 . Many new sulfonamide derivatives, such as E7070 (indisulam), have shown substantial antitumor activity via different mechanisms [7][8][9][10][11][12][13][14][15][16][17] . It was also reported to selectively accumulate within cancerous cells.…”
Section: Introductionmentioning
confidence: 99%